Importance of use of operating models in the decision making: A Case Study - Hameed, Zainab Alaa (Al-Ghary Journal of Economic and Administrative Sciences, 2024)
The field of operations research is represented in an attempt to find mathematical models that express the real problem, with an attempt to develop mathematical tools that enable the solution of these models, with the aim of reaching the optimal alternative among the available alternatives to solve the problem, Hence the idea of ​​our study, which is mainly focused on clarifying the importance of programming objectives and integer programming models in productive decision-making. These models were applied to Al-Tariq Food Products Company and General Car and Equipment Manufacturing Company, during the period 2019-2021. يتمثل مجال بحوث العمليات في محاولة إيجاد نماذج رياضية تعبر عن المشكلة الحقيقية، مع محاولة تطوير أدوات رياضية تمكن من حل هذه النماذج، بهدف الوصول إلى البديل الأمثل من بين البدائل المتاحة لحل المشكلة، ومن هنا جاءت فكرة دراستنا التي تركز بشكل أساسي على توضيح أهمية أهداف البرمجة ونماذج البرمجة الصحيحة في اتخاذ القرارات الإنتاجية، وقد تم تطبيق هذه النماذج على شركة الطارق للمواد الغذائية والشركة العامة لتصنيع السيارات والمعدات، خلال الفترة 2019-2021.